The New Brazilian Mediascape : Television Production in the Digital Streaming Age - Carter, Eli Lee (Book collections on Project MUSE., 2020)
"In this book, Eli Carter explores the ways in which the movement away from historically popular telenovelas toward new television and internet series is creating dramatic shifts in how Brazil imagines itself as a nation, especially within the context of an increasingly connected global mediascape"--